Nanoporous Ni(OH)2 Thin Film on 3D Ultrathin-Graphite Foam for Asymmetric Supercapacitor - Ji, Junyi; Zhang, Li Li; Ji, Hengxing; Li, Yang; Zhao, Xin; Bai, Xin; Fan, Xiaobin; Zhang, Fengbao; Ruoff, Rodney S (ACS nano, 2013)
Nanoporous nickel hydroxide (Ni(OH)2) thin film was grown on the surface of ultrathin-graphite foam (UGF) via a hydrothermal reaction. The resulting free-standing Ni(OH)2/UGF composite was used as the electrode in a supercapacitor without the need for addition of either binder or metal-based current collector. The highly conductive 3D UGF network facilitates electron transport and the porous Ni(OH)2 thin film structure shortens ion diffusion paths and facilitates the rapid migration of electrolyte ions. An asymmetric supercapacitor was also made and studied with Ni(OH)2/UGF as the positive electrode and activated microwave exfoliated graphite oxide (‘a-MEGO’) as the negative electrode. The highest power density of the fully packaged asymmetric cell (44.0 kW/kg) was much higher (2–27 times higher), while the energy density was comparable to or higher, than high-end commercially available supercapacitors. This asymmetric supercapacitor had a capacitance retention of 63.2% after 10 000 cycles.